Incidencia de la dramatización como estrategia metodológica en el desarrollo del lenguaje de los alumnos del centro de educación inicial Doralina Rivera Navarro de la parroquia Puerto Bolívar del cantón Machala, provincia de El Oro periodo lectivo 2014 – 2015. - Zambrano Vélez, Gloria Estefanía (2015)
At the Center for Early Education Doralina Navarro Rivera, the Puerto Bolívar Parish, Canton Machala, El Oro Province, investigating the impact of dramatization was performed as Methodological Strategy Language Development students Early Education Center Doralina Navarro Rivera the Puerto Bolívar Parish, Canton Machala, El Oro Province academic year 2014 - 2015, the overall objective was: Identify the procedures applied by teachers for using dramatization as a learning strategy in intra and extra activities class of students and early childhood education early Education Center Doralina Rivera Navarro. The results were achieved through surveys at 8 teachers and the observation guide to different students of the institution, it is important to emphasize that what you want to suggest to help eradicate this problem is to apply a seminar-workshop given to professors Early Education Center Doralina Navarro Rivera to have new ideas and knowledge about the impact of Drama in students for better cognitive development in the teaching-learning process.